Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.2337/diacare.15.4.528
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria Associated With Diabetic Neuropathy

Abstract: Microalbuminuria is independently associated with diabetic neuropathy. This association lends support to the theory of a vascular etiology for diabetic distal symmetrical neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Our study groups were carefully characterized and because of potential links with AN they were matched for age, gender, diabetes duration, and smoking status [16,17]. In keeping with the results of previous studies [18][19][20][21][22], microalbuminuric and normoalbuminuric groups showed differences in some clinical variables (Table 2). Our comparison of autonomic function in MA and NA groups excludes, through careful matching, the effects of age, gender, diabetes duration, and smoking status but there are various reasons why differences in autonomic function might not be explained only by differences in AER.…”
Section: Discussionmentioning
confidence: 89%
“…Our study groups were carefully characterized and because of potential links with AN they were matched for age, gender, diabetes duration, and smoking status [16,17]. In keeping with the results of previous studies [18][19][20][21][22], microalbuminuric and normoalbuminuric groups showed differences in some clinical variables (Table 2). Our comparison of autonomic function in MA and NA groups excludes, through careful matching, the effects of age, gender, diabetes duration, and smoking status but there are various reasons why differences in autonomic function might not be explained only by differences in AER.…”
Section: Discussionmentioning
confidence: 89%
“…The association of albuminuria with the presence of neuropathy has been demonstrated in a number of studies involving IDDM subjects [48,49], but this is the first demonstration in patients with NIDDM. Although the exact pathogenesis of diabetic neuropathy is still under question, morphological studies suggest that an ischaemic aetiology is involved in the pathogenesis of diabetic polyneuropathy [50].…”
Section: Discussionmentioning
confidence: 97%
“…Another limitation of this study is that it did not evaluate the effects of these drug–drug interactions in the target patient population. Diabetes is frequently complicated by renal and hepatic impairment 18, 19. Since the metabolism and clearance of drugs may be different in patients with renal and hepatic impairment, future studies are needed to evaluate the PK and safety of mirogabalin coadministered with probenecid or cimetidine in these patients.…”
Section: Discussionmentioning
confidence: 99%